(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Preschool education lays the foundation for a child’s academic, social, and emotional development. In recent years, educators and researchers have increasingly recognized the profound impact that music can have on preschoolers. Music, with its captivating melodies and rhythmic patterns, plays a pivotal role in enhancing various aspects of early childhood education.